Contribuições metodológicas para criação de bibliotecas digitais de livros raros: aplicação na coleção Brasiliana da UFMG - Júlia Rocha Ribeiro (2021)
Library managers, in the current technological context, have shown great interest in digital libraries of rare and old books. Issues of preservation, dissemination and research are factors that permeate the existence of physical libraries and the implementation of digital libraries. In this respect, the digitization process of rare books works with the preservation and dissemination of this material, with the argument that the process will benefit the durability of the books, allowing access to the content, without the need to handle the original. Another argument in favor of digitizing rare works is the fact that it facilitates access to and knowledge of books, making them available for remote consultation and at the reach of online researchers. Thus, the publication of these works in digital format helps to preserve the originals and increases the availability of access. Considering that UFMG's Rare Works Division does not currently have a digital library, this research creates a methodology for digitizing rare collections. Based on analysis of documents and literature related to the topic and a case study of digitization and online availability, from the Brasiliana Collection at UFMG. The intention is that this methodology is a satisfactory and low cost model, in order to be generalizable and applied in other libraries. From searches of databases and websites, documents and reports of experiences were obtained that favored the creation of key points, which were applied in the Brasiliana collection of UFMG. With this, practical results of the research were obtained, digitizing and making this collection available on a website. These points are the main elements for digitizing and making available a collection of rare books online. In this way, there is the construction of a digital library for rare books at UFMG, with possibilities of applications for other libraries that are interested in developing in the digital scope.